Regioselective O-Glycosylation of Nucleosides via the Temporary 2',3'-Diol Protection by a Boronic Ester for the Synthesis of Disaccharide Nucleosides - Someya, Hidehisa (J Vis Exp, 2018)
Disaccharide nucleosides, which consist of disaccharide and nucleobase moieties, have been known as a valuable group of natural products having multifarious bioactivities. Although chemical O-glycosylation is a commonly beneficial strategy to synthesize disaccharide nucleosides, the preparation of substrates such as glycosyl donors and acceptors requires tedious protecting group manipulations and a purification at each synthetic step. Meanwhile, several research groups have reported that boronic and borinic esters serve as a protecting or activating group of carbohydrate derivatives to achieve the regio- and/or stereoselective acylation, alkylation, silylation, and glycosylation. In this article, we demonstrate the procedure for the regioselective O-glycosylation of unprotected ribonucleosides utilizing boronic acid. The esterification of 2',3'-diol of ribonucleosides with boronic acid makes the temporary protection of diol, and, following O-glycosylation with a glycosyl donor in the presence of p-toluenesulfenyl chloride and silver triflate, permits the regioselective reaction of the 5'-hydroxyl group to afford the disaccharide nucleosides. This method could be applied to various nucleosides, such as guanosine, adenosine, cytidine, uridine, 5-metyluridine, and 5-fluorouridine. This article and the accompanying video represent useful (visual) information for the O-glycosylation of unprotected nucleosides and their analogs for the synthesis of not only disaccharide nucleosides, but also a variety of biologically relevant derivatives.